Small numbers of Chlamydia trachomatis elementary bodies on slides detected by the polymerase chain reaction. - Gilroy, C. B. (1992)
A method is described in which smears on slides, which had been examined previously in a direct fluorescence antibody (DFA) test for Chlamydia trachomatis, were tested by the polymerase chain reaction (PCR). Twenty four (73%) of 33 smears which contained fewer than 10 elementary bodies when examined by the DFA test were positive by the PCR. Of the nine negative smears, seven contained only one or two elementary bodies. However, single elementary bodies were detected by the PCR in seven of the 24 positive samples. Fifteen smears were negative by both methods. The ability to detect small numbers of elementary bodies by the PCR and its specificity for negative smears indicates its potential for retrospective analysis of stored, archival smears on slides.